Patients’ and family members’ knowledge, attitudes and perceived family support for SMBG in type 2 diabetes: a fuzzy-set qualitative comparative analysis - Jun Lu; Xiaohong Li; Qian Zhao; Ying Guo; Xinying Yu; Yuheng Feng; Yuxi Zhao (BMJ Open)
Aims and objectives To examine the combined effects of the patient’s and family members’ knowledge, attitudes and perceived family support on self-monitoring of blood glucose (SMBG) behaviour of patients with type 2 diabetes.Design A cross-sectional design using the framework of knowledge–attitude–behaviour (KAB) combined with family support.Setting Shanghai, China.Participants Seventy type 2 diabetes patient–family member dyads recruited from 26 residential committees in Shanghai were investigated. Twenty-three health providers were interviewed.Primary outcome measures The knowledge, attitudes and perceived family support of patients’ and their family members’ data were measured through scales. Combined effects were analysed by a fuzzy-set qualitative comparative analysis (fsQCA) using fsQCA V.3.0. Other analyses and calculations were performed by STATA V.14.0.Results SMBG was very poor (20%), and behaviour was characterised by ‘multiple complications,’ and ‘all paths lead to the same destination’ for patients. There were two solution paths toward patients’ SMBG (solution coverage=0.4239, solution consistency=0.7604). One path was the combination of ‘patients with low risk perception, the patients’ and family members’ perceived negative support’, the other was the combination of ‘patients with high risk perception, the patients’ perceived negative support’. In both paths, basic knowledge serves as an auxiliary condition.Conclusion The study revealed that for patients with high and low risk perceptions that are relatively difficult to change, we could strengthen family support to achieve the desired SMBG behaviour. Knowledge is not a prerequisite to achieving SMBG. Moreover, negative family support plays a crucial role. Perceived family support by patients is more important than perceived family support by family members, which suggests that family members should improve support for patients so that the patients can perceive more family support.